Simulação de falta no enrolamento de campo de geradores síncronos pelo método dos elementos finitos - Schmidt, André da Cunha (2017)
This work presents a study about rotor interturn short detection – also called as field coils – of synchronous generators through simulation of a typical machine of thermoelectrical power plants moved by heavy duty stationary turbines (not aeroderivative). It is applied a known detection technique, the air gap magnetic flux variation analysis, adapted to a computational simulation model. The simulation is performed by the finite elements method in the software Maxwell supported by its electrical machines modelling package RMXprt, both from Ansys property. In the study, some fault models are proposed, to observe the effect of those faults in the operational parameters of the machine. In the biggest part of the cases, these effects are hard to be observed during the operational routine, it will be analyzed the air gap magnetic flux variation and the machine’s output parameters in many distinct scenarios.